A sodium ion battery electrolyte and its application

By adding surfactant and vinyl sulfate to the sodium ion battery electrolyte, the problem of insufficient electrolyte in the separator infiltration ability is solved, the charge and discharge performance and safety are improved, and the gas production in the chemical formation stage is reduced.

CN113871714BActive Publication Date: 2025-03-25ZHANGJIAGANG GUOTAI HUARONG NEW CHEM MATERIALS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202010615704.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-06-30
Publication Date
2025-03-25
Estimated Expiration
2040-06-30

AI Technical Summary

Technical Problem

The existing sodium ion battery electrolyte has insufficient wetting ability on the separator, which affects the charge and discharge performance.

Method used

An electrolyte containing a non-aqueous organic solvent, sodium salt and electrolyte additive is used. The electrolyte additive consists of surfactant and vinyl sulfate, which accounts for 0.1% to 5% of the total mass of the electrolyte and vinyl sulfate account for 0.1% to 5% of the total mass of the electrolyte.

Benefits of technology

It improves the wetting property of the electrolyte on the separator, enhances the charging and discharging performance and safety of sodium ion batteries, reduces the gas production in the chemical formation stage, and shortens the battery aging time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The present invention relates to an electrolyte of a sodium ion battery and its application, wherein the electrolyte comprises a non-aqueous organic solvent, a sodium salt and an electrolyte additive, wherein the electrolyte additive comprises a surfactant and vinyl sulfate, wherein the surfactant accounts for 0.1% to 5% of the total mass of the electrolyte, and the vinyl sulfate accounts for 0.1% to 5% of the total mass of the electrolyte. The electrolyte of the sodium ion battery of the present invention has high wettability, produces less gas in the formation stage of the sodium ion battery, and has excellent charge and discharge performance and safety performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemistry, and in particular relates to an electrolyte of a sodium ion battery and an application thereof. Background Art

[0002] The widespread use of lithium-ion batteries has led to a sharp increase in the demand for lithium. However, lithium is a rare metal, and its production and recycling technologies are not mature enough, which constitutes a shortcoming for future large-scale applications. Therefore, it is particularly important to develop new high-performance secondary battery systems. Sodium and lithium are both in the first cycle and have similar properties in terms of valence state and reaction activity. At the same time, sodium is abundant in the earth's crust and is easy to produce and recycle. Therefore, sodium-ion batteries constructed with sodium instead of lithium have higher potential economic and environmental benefits.

[0003] The working mechanism of sodium ion secondary batteries based on non-aqueous electrolytes is similar to that of lithium ion batteries. Sodium ions are reversibly embedded and released at the positive and negative electrodes during the charge and discharge process. The electrolyte is a carrier for the transmission of sodium ions, and is also a medium for the reversible reaction of active materials in the electrode process. Its electrochemical properties are closely related to the specific capacity and cycle performance of the battery. At present, the non-aqueous electrolytes used in sodium ion batteries are mainly carbonate solutions. Among them, the electrolyte prepared by the mixed solvent of ethylene carbonate and propylene carbonate has good electrochemical stability and chemical stability to sodium metal, and has been widely recognized and applied. However, ethylene carbonate and propylene carbonate usually have high surface tension, and the prepared electrolyte does not have good wetting ability on the diaphragm, which affects the charge and discharge performance of the sodium battery.

[0004] In order to improve the wettability of the electrolyte and the diaphragm, a surfactant can be added to the diaphragm. For example, Chinese patent CN110391386A mentions adding polyethers such as P123 in the preparation of the diaphragm. The obtained diaphragm meets the requirements in terms of mechanical strength, thermal stability, electrode interface stability, electrolyte wettability and other conventional properties. At the same time, the electrochemical performance, rate performance and cycle stability of the lithium battery system are improved. Chinese patent CN109183037A provides a method of chemically polishing a metal lithium sheet using a polymer P123. The capacity retention rate of a lithium battery prepared from a lithium sheet treated by this method is significantly improved. However, adding polymer compounds such as P123 to sodium ion batteries will deteriorate the charge and discharge performance of sodium ion batteries. This may be because compared with traditional lithium-ion battery negative electrode materials, the radius of sodium ions is larger, and the interlayer spacing or pores of the matching sodium ion negative electrode materials are large. High molecular polymers such as P123 in the electrolyte are more easily adsorbed on the positive and negative electrode surfaces, blocking the pores of the positive and negative electrodes. Therefore, it is easier to affect the normal entry and exit of sodium ions in the sodium ion battery, showing an increase in polarization. As the content of high molecular polymers such as P123 increases, the polarization becomes larger and larger.

[0005] Therefore, how to improve the wetting ability of the electrolyte of the sodium ion battery to the diaphragm while having little impact on the charge and discharge performance of the battery remains to be solved. Summary of the invention

[0006] The object of the present invention is to provide a sodium ion battery electrolyte having good electrolyte wettability to a diaphragm, good charge and discharge performance and good safety.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] The first aspect of the present invention provides an electrolyte for a sodium ion battery, comprising a non-aqueous organic solvent, a sodium salt and an electrolyte additive, wherein the electrolyte additive comprises a surfactant and diethylene sulfate (DTD), wherein the surfactant accounts for 0.1% to 5% of the total mass of the electrolyte, and the diethylene sulfate accounts for 0.1% to 5% of the total mass of the electrolyte.

[0009] Preferably, the surfactant is a nonionic surfactant. Nonionic surfactants have little interference with ion movement and redox reactions, and are highly stable and have good compatibility. In addition, since the nonionic surfactant in the electrolyte is adsorbed on the electrode surface after injection, the decomposition of vinyl sulfate on the electrode surface can be inhibited.

[0010] Preferably, the nonionic surfactant accounts for 0.2% to 3% of the total mass of the electrolyte, and more preferably 0.2% to 1%. Using the preferred amount of nonionic surfactant can enable the electrolyte to obtain ideal wetting ability, and the usage amount is small, saving costs.

[0011] In order to improve the problem of large polarization caused by adding surfactants to the electrolyte of sodium ion batteries, the inventors tried to add film-forming additives vinylene carbonate (VC) and fluoroethylene carbonate (FEC), but found that VC was not suitable for the sodium ion battery system; fluoroethylene carbonate (FEC) can be used in the sodium ion battery system, but the use of this substance together with non-ionic surfactants such as P123 will inhibit the battery capacity. FEC produces HF through non-electrochemical reactions, the interface impedance increases, and ultimately leads to battery capacity decay.

[0012] Finally, the inventors used a combination of surfactant and dithiothreitol (DTD) to achieve good wettability of the electrolyte with the diaphragm and the positive electrode, while also improving the charge and discharge performance and safety of the battery. They can also reduce the gas production in the formation stage of the sodium ion battery and shorten the aging time from the filling and sealing of the sodium ion battery to the formation stage.

[0013] In the present invention, when the amount of vinyl sulfate used is 0.5%-5% of the total mass of the electrolyte, a stable SEI film can be formed on the surface of the positive and negative electrodes, reducing the impedance of the sodium ion battery, thereby improving the performance of the sodium ion battery. If the amount of vinyl sulfate used is less than 0.5% of the total mass of the electrolyte, the generated SEI film is unstable; if the amount of vinyl sulfate used is more than 5% of the total mass of the electrolyte, the generated positive electrode SEI protective film is too thick and dense, which will have an adverse effect on the capacity of the sodium ion battery. In addition, since the decomposition of ethyl acetate in the formation stage of the sodium ion battery will cause the sodium ion battery to produce a large amount of gas in the formation stage, thereby causing battery bloating and reducing the safety performance of the battery, when the amount of vinyl sulfate used exceeds 5% of the total mass of the electrolyte, the gas production will also increase greatly.

[0014] Preferably, the vinyl sulfate accounts for 0.5% to 2% of the total mass of the electrolyte. Using the preferred amount of vinyl sulfate can further reduce the gas production. Preferably, the nonionic surfactant is a high molecular polymer.

[0015] Specifically, the high molecular polymer includes, but is not limited to, polyether P123 and polyether F127.

[0016] Preferably, the non-aqueous organic solvent is a mixture of ethylene carbonate and propylene carbonate. The electrolyte prepared from the mixed solvent of ethylene carbonate and propylene carbonate has good electrochemical stability and chemical stability to sodium metal.

[0017] More preferably, the volume ratio of the ethylene carbonate to the propylene carbonate is 1:0.8-1.2.

[0018] Preferably, the sodium salt is one or more of sodium hexafluorophosphate, sodium perchlorate, sodium tetrafluoroborate, sodium bis(trifluoromethylsulfonyl)imide, and sodium bis(fluorosulfonyl)imide.

[0019] More preferably, the concentration of the sodium salt is 0.1-2 mol / L.

[0020] According to a specific and preferred embodiment, the sodium salt is sodium hexafluorophosphate, and the concentration is 1 mol / L.

[0021] The second aspect of the present invention also provides an application of the electrolyte in a sodium ion battery.

[0022] The third aspect of the present invention also provides a sodium ion battery, comprising a positive electrode, a negative electrode, a separator and the electrolyte.

[0023] According to a specific embodiment, the positive electrode material is metallic sodium, and the negative electrode material is sodium vanadium phosphate.

[0024] The electrolyte of the sodium ion battery of the present invention can improve the wettability of the diaphragm and the positive electrode, and shorten the aging time from the filling and sealing of the sodium ion battery to the formation; the solid electrolyte interface film (SEI film) formed by the electrolyte of the sodium ion battery of the present invention on the positive and negative electrodes is stable and low-impedance, effectively solving the problem of sodium dendrites and effectively inhibiting gas production in the formation stage, thereby improving the cycle performance of the sodium ion battery and improving the safety performance of the sodium ion battery. Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0025] The electrolyte of the sodium ion battery of the present invention has high wettability, produces little gas during the formation stage of the sodium ion battery, and has excellent charge and discharge performance and safety performance. DETAILED DESCRIPTION

[0026] The present invention is further described below in conjunction with the examples. However, the present invention is not limited to the following examples. The implementation conditions used in the examples can be further adjusted according to the different requirements of specific use, and the implementation conditions not specified are conventional conditions in the industry.

[0027] The reagents and raw materials used in the present invention are commercially available.

[0028] 1. Test the electrolyte adsorption percentage on the diaphragm

[0029] Prepare electrolyte: Ethylene carbonate and propylene carbonate are mixed evenly in a volume ratio of 1:1, sodium hexafluorophosphate is added, and the concentration of sodium hexafluorophosphate is controlled to be 1 mol / L. The mixture is divided into 11 parts on average, and electrolyte additives are added according to the composition and amount (mass percentage in the electrolyte) of the electrolyte additives of Comparative Example 1 and Examples 1 to 10 in Table 1, respectively, to obtain the electrolytes of Comparative Example 1 and Examples 1 to 10.

[0030] The Celgard 2340 diaphragm was cut into φ16 cm discs, weighed, and marked as M0; the diaphragm discs were respectively placed in the electrolytes of Examples 1 to 10 and Comparative Example 1, and left for 2 hours. The diaphragm was taken out from the electrolyte, and the electrolyte on the diaphragm was gently adsorbed with filter paper, and weighed again, marked as M; the electrolyte adsorption percentage on the diaphragm was calculated respectively, and the test results are shown in Table 1.

[0031] Electrolyte adsorption percentage = (M-M0) / M0*100%

[0032] Table 1

[0033]

[0034]

[0035] 2. Test the gas production of sodium ion batteries at 25°C, the battery capacity percentage and short circuit time after 100 cycles of 1C charge and discharge

[0036] Prepare electrolyte: Ethylene carbonate and propylene carbonate are mixed evenly in a volume ratio of 1:1, sodium hexafluorophosphate is added, and the concentration of sodium hexafluorophosphate is controlled to be 1 mol / L. Electrolyte additives are added according to the composition and amount (mass percentage in the electrolyte) of the electrolyte additives of each embodiment and each comparative example in Table 2 to obtain electrolytes of each comparative example and each embodiment.

[0037] The electrolytes of the comparative examples and the embodiments were respectively assembled with the positive and negative electrodes according to conventional processes into sodium ion batteries. The negative electrode material was hard carbon and the positive electrode material was sodium vanadium phosphate. The sodium ion batteries prepared in the embodiments and the comparative examples were tested at 25°C and 0.1C charge and discharge. The volume of the battery before and after formation and the discharge capacity of the battery were recorded, and the gas production of the battery was calculated. The gas production results are shown in Table 2. The discharge capacity of the battery was recorded after 100 cycles of charge and discharge at 1C at 25°C. The test results are shown in Table 2.

[0038] Battery formation gas production (ml / Ah) = (battery volume after formation - battery volume before formation) / battery discharge capacity × 100%.

[0039] Capacity percentage (%) = discharge battery capacity after 100 cycles / average discharge battery capacity during the first 5 cycles × 100%.

[0040] The electrolytes of the comparative examples and the examples were assembled with sodium sheets into sodium symmetrical button cells, and the glass fiber diaphragm was selected as the separator. The sodium ion button cells prepared in the examples and the comparative examples were tested at 25°C with a current of 1 mA / cm 2 Discharge at a constant current, record the time from the start of the test to the short circuit, and the test results are shown in Table 2. The short circuit time is " / ", indicating that no short circuit occurred during the test.

[0041] Table 2

[0042]

[0043]

[0044] 3. Test the battery capacity percentage of sodium ion batteries after 100 cycles of 1C charge and discharge at 25°C and 45°C

[0045] Prepare electrolyte: Ethylene carbonate and propylene carbonate are mixed evenly in a volume ratio of 1:1, sodium hexafluorophosphate is added, and the concentration of sodium hexafluorophosphate is controlled to be 1 mol / L, and electrolyte additives are added according to the composition and amount (mass percentage in the electrolyte) of the electrolyte additives of the embodiments and comparative examples in Table 3, respectively, to obtain electrolytes of the comparative examples and embodiments.

[0046] The electrolytes of the comparative examples and the embodiments were respectively assembled into sodium ion batteries with the positive and negative electrodes according to conventional processes. The negative electrode material was hard carbon and the positive electrode material was sodium vanadium phosphate. The discharge capacity of the battery was recorded by 100 cycles of charge and discharge at 1C at 25°C and 45°C. The test results are shown in Table 3.

[0047] Capacity percentage (%) = discharge battery capacity after 100 cycles / average discharge battery capacity during the first 5 cycles × 100%.

[0048] Table 3

[0049]

[0050] PST: 1-propenyl-1,3-sultone;

[0051] DTD: diethyl sulphate;

[0052] PS: 1,3-propane sultone;

[0053] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. An electrolyte for a sodium ion battery, comprising a non-aqueous organic solvent, a sodium salt and an electrolyte additive, characterized in that: The non-aqueous organic solvent is a mixture of ethylene carbonate and propylene carbonate, the electrolyte additive is composed of a surfactant and vinyl sulfate, the surfactant accounts for 0.2% to 0.5% of the total mass of the electrolyte, the vinyl sulfate accounts for 0.5% to 2% of the total mass of the electrolyte, and the surfactant is polyether P123 and / or polyether F127.

2. The electrolyte according to claim 1, characterized in that: The volume ratio of the ethylene carbonate to the propylene carbonate is 1:0.8-1.

2.

3. The electrolyte according to claim 1, characterized in that: The sodium salt is one or more of sodium hexafluorophosphate, sodium perchlorate, sodium tetrafluoroborate, sodium bis(trifluoromethylsulfonyl)imide and sodium bis(fluorosulfonyl)imide.

4. The electrolyte according to claim 3, characterized in that: The concentration of the sodium salt is 0.1-2 mol / L.

5. Use of the electrolyte according to any one of claims 1 to 4 in a sodium ion battery.

6. A sodium ion battery comprising a positive electrode, a negative electrode, a separator and the electrolyte according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Method for chemically polishing lithium metal by virtue of high-molecular polymer

    CN109183037A

  • Composite diaphragm and preparation method and use thereof

    CN110391386A

  • Electrolyte of sodium ion battery, and preparation method and application of electrolyte

    CN106920988A

  • Nonaqueous electrolyte solution for sodium secondary battery, and sodium secondary battery

    JP2016181467A